Prosthetic valve endocarditis caused by Corynebacterium afermentans subsp. lipophilum (CDC coryneform group ANF-1). - Sewell, D L (1995)
Corynebacteria are important causes of endocarditis in individuals with valvular prostheses. We report the first published case of prosthetic valve endocarditis caused by the newly defined species Corynebacterium afermentans subsp. lipophilum (former CDC coryneform group ANF-1). The isolate was recovered from a perivalvular abscess specimen and 5 of 15 Bactec blood cultures after 7 to 15 days of incubation. The isolation, identification, and susceptibility testing of Corynebacterium species are discussed.